Metal-doped modified SiOx-based composite negative electrode material and preparation method and application thereof
By doping metals that can form alloys with Li in SiOx, forming metal-doped modified SiOx-based composite anode material, the problems of low initial efficiency and poor cycle stability in lithium-ion batteries are solved, and higher cycles are achieved Stability and lithium storage performance.
Patent Information
- Application Number
- CN202411590922.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
SiOx has a low initial Coulomb efficiency, conductivity and ion diffusion coefficient in lithium-ion batteries, and volume expansion during the cycle leads to pulverization and unstable solid electrolyte interfaces, affecting lithium storage performance.
By doping metals that can form alloys with Li into SiOx, metal-doped modified SiOx-based composite anode material is formed, and the particles are loaded with metal clusters and doped into the solid electrolyte interface, promoting silicon-based particles and single-wall carbon nanometers Interface coupling between tubes.
The cyclic stability of SiOx-based negative electrode is significantly improved, the adsorption of lithium ions and the interfacial ion transfer rate are enhanced, and the powdering problems caused by stress concentration and volume expansion are reduced.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery electrode materials, and in particular relates to a silicon-based negative electrode material, a preparation method thereof, and a lithium ion battery or lithium ion secondary battery containing the same, and specifically relates to a metal-doped modified SiO x Based composite negative electrode material and its preparation method and application. Background Art
[0002] The rapid development of various electronic products, electric vehicles and large-scale energy storage equipment has promoted the rapid iteration of energy storage equipment or devices. Lithium-ion secondary batteries have been widely used due to their stable performance and mature technology, and have alleviated safety and environmental pollution issues during the iteration process. Compared with traditional batteries, lithium-ion secondary batteries have the advantages of high energy density and good cycle performance, and have become the backbone of the energy storage field, but it is still difficult to meet the growing market demand, so it is necessary to develop and manufacture lithium-ion batteries with better comprehensive performance.
[0003] Graphite anodes are the mainstay of commercial lithium-ion secondary batteries, but the theoretical specific capacity of graphite is low (372 mAh / g) and is about to reach its energy density ceiling. Replacing graphite anodes with high-capacity silicon-based anodes is one of the most promising strategies to significantly increase the energy density of lithium-ion batteries (LIBs).
[0004] Among various silicon-based materials, micron-sized silicon dioxide (SiO x ) has attracted wide attention due to its relatively high specific capacity (~2600mAh / g), small volume expansion (~200%), low specific surface area, high tap density and low production cost. x Base negative electrode materials are one of the main current research directions.
[0005] However, SiO x There are also many problems in the application process, such as SiO x The lithium silicate salts and Li 2 O will lead to lower initial Coulombic efficiency, conductivity and ion diffusion coefficient, and reduce the electrochemical reaction kinetics. In addition, SiO x There is still a relatively large volume expansion during the cycle, which can easily cause SiO x The pulverization of the negative electrode, the appearance of an unstable solid electrolyte interface (SEI), the increase of side reactions, and the loss of electrical contact of the electrode material to form "dead silicon" and other conditions lead to the rapid attenuation of lithium storage performance, affecting the SiO x Rapid commercial application.
[0006] Due to the above problems, silicon dioxide (SiOx ) can only be mixed with graphite in a low ratio in the negative electrode of commercial lithium batteries, which makes it difficult to truly improve the energy density of commercial lithium batteries. Therefore, how to effectively x The electrical conductivity and ionic conductivity can be improved, and the pulverization problem caused by its volume expansion can be alleviated, which is of research significance for the future development of silicon-based negative electrode materials and lithium-ion batteries. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention proposes a metal-doped modified SiO x Composite negative electrode material and preparation method thereof, by using a metal capable of forming an alloy with Li to form a SiO x Doping modification is performed. The metal clusters loaded on the surface of the particles can be in-situ doped into the solid electrolyte interface (SEI) during the cycle process, forming an alloy with lithium ions to greatly enhance the adsorption of lithium ions in the electrolyte and the ion transfer rate on the interface, and can also promote the interface coupling between silicon-based particles and single-walled carbon nanotubes; in addition, the metal elements doped into the interior of the silicon-based particles can effectively inhibit disproportionation and improve the mass transfer rate within the silicon-based particles, homogenize the ion concentration field and electric field, reduce stress concentration, and effectively improve the SiO x Cycling stability of the negative electrode.
[0008] Furthermore, the present invention also provides the metal-doped modified SiO x Application of composite negative electrode materials in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
[0009] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0010] A metal-doped modified SiO x Preparation method of composite negative electrode material based on SiO x Doping modification is carried out by reacting the corresponding metal or metal oxide with SiO x After dry mixing of the powders, the mixture with a certain particle size is subjected to high temperature heat treatment to obtain high-performance SiO x Based composite negative electrode materials.
[0011] The preparation method specifically comprises the following steps:
[0012] 1) dry-mixing silicon dioxide and metal or metal oxide in a certain proportion to obtain a mixture I;
[0013] 2) Place the mixture I in a tube furnace, perform high temperature heat treatment under inert atmosphere and certain temperature and pressure conditions, and then cool it naturally to room temperature (25±5°C) to obtain metal-doped modified SiO xBased composite negative electrode materials.
[0014] Furthermore, in step 1), the silicon dioxide (SiO x ) median particle size D 50 1 to 30 μm, wherein the atomic ratio of silicon and oxygen in silicon oxide is (0.2 to 5):1; or, the silicon oxide SiO x The atomic percentage of silicon is 61% to 64%, preferably 62.5%.
[0015] Furthermore, in step 1), the molar ratio of silicon dioxide to metal or metal oxide is 1000:1 to 1:99, preferably 200:1 to 1:20.
[0016] Furthermore, the metal or metal oxide described in step 1) includes but is not limited to Bi, Bi 2 O 3 、Ge、GeO 2 、Sb、SbO 2 、Sn、SnO 2 , Al or Al 2 O 3 Furthermore, in step 1), during the dry mixing, a carbon source material may be added.
[0017] Furthermore, in step 1), when adding the carbon source material, the mass ratio of the carbon source material to silicon oxide is 1:(1-10).
[0018] Furthermore, the carbon source material in step 1) is one or more of coal tar pitch, petroleum pitch, coal-based mesophase pitch, glucose, starch, phenolic resin, chitosan, urea, sucrose and the like.
[0019] Furthermore, the equipment used for dry mixing in step 1) is a VC mixing equipment, a V-type mixing equipment or a high-speed ball mill mixing equipment.
[0020] Furthermore, during the dry mixing in step 1), grinding balls are added for ball milling mixing, the dry mixing time is 0.05 to 6 hours, and the ball milling speed is 50 to 2000 rpm.
[0021] Further preferably, during dry mixing in step 1), the grinding balls used are zirconium beads; the amount of zirconium beads added is such that the mass ratio of the mixed material to the zirconium beads is 1:1 to 1:8, and the size of the zirconium beads is 0.1 to 5 mm.
[0022] Further preferably, the mixed material is a material obtained by mixing silicon monoxide powder and metal or metal oxide, or a material obtained by mixing silicon monoxide powder, metal or metal oxide and a carbon source material.
[0023] Furthermore, the high temperature heat treatment in step 2) is high temperature sintering.
[0024] Further preferably, during the high temperature heat treatment in step 2), the inert atmosphere is formed by a mixed gas of one or more of nitrogen, argon and helium; the gas flow rate under the inert atmosphere is 0.2 to 5 L / min, and the ventilation time is 0.5 to 20 h.
[0025] Furthermore, the high temperature heat treatment in step 2) is to keep the temperature at 200°C to 1000°C for 0.01h to 5h.
[0026] Further preferably, the high temperature heat treatment in step 2) is to keep the temperature at 200°C to 400°C or 400°C to 1000°C for 0.01h to 5h.
[0027] Further preferably, the procedure for the high temperature heat treatment in step 2) can also be: first keep the temperature at 200°C to 400°C for 0.01h to 3h, then heat to 400°C to 1000°C and keep the temperature for 0.01h to 5h, with a heating rate of 1 to 10°C / min.
[0028] Further preferably, the pressure during the high temperature heat treatment in step 2) is (0.9 to 1.2) atmospheres, preferably normal pressure.
[0029] Furthermore, in step 2), after the mixture I is subjected to high temperature heat treatment, the excess metal, excess metal oxide or SiO2 remaining on the surface of the prepared composite negative electrode material during the preparation process can be removed by acid washing. 2 After pickling, rinse with water to remove residual acid on the surface of the solid product, and then dry to obtain the final product.
[0030] Furthermore, during pickling, the acid used is one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, hydrofluoric acid, etc., and the concentration of the acid used can be 0.05-5 mol / L, or other common industrial pickling concentrations.
[0031] Furthermore, the pickling time is 1 to 5 hours.
[0032] Furthermore, during pickling, ultrasonic treatment is also carried out at room temperature (25±5° C.), with an ultrasonic power of 200 to 1500 W and an ultrasonic time of 1 to 10 h.
[0033] Furthermore, when washing with water, the pH value is greater than or equal to 5 and less than or equal to 8.
[0034] Furthermore, the drying is carried out using a blast drying oven, a vacuum drying oven, or a box furnace, etc., the drying temperature is 60-100° C., and the drying time is 12h-36h.
[0035] As another preferred technical solution, the metal-doped modified SiO x The method for preparing a composite negative electrode material comprises the following steps:
[0036] (1) dry-mixing silicon dioxide and metal or metal oxide in a certain proportion to obtain a mixture I;
[0037] (2) placing the mixture I in a tube furnace, performing a high temperature heat treatment under an inert atmosphere and certain temperature and pressure conditions, and then naturally cooling the mixture to room temperature (25±5° C.) to obtain a composite material;
[0038] (3) dry-mixing the composite material of step (2) and the carbon source material in a certain proportion to obtain a mixture II;
[0039] (4) Place the mixture II in a tube furnace, perform high temperature heat treatment under an inert atmosphere and certain temperature and pressure conditions, and then cool it naturally to room temperature (25±5°C) to obtain metal-doped modified SiO x Based composite negative electrode materials.
[0040] Furthermore, in step (1), the silicon dioxide (SiO x ) median particle size D 50 1 to 30 μm, wherein the atomic ratio of silicon and oxygen in silicon oxide is (0.2 to 5):1; or, the silicon oxide SiO x The atomic percentage of silicon is 61% to 64%, preferably 62.5%.
[0041] Furthermore, in step (1), the molar ratio of silicon monoxide to metal or metal oxide is 1000:1 to 1:99, preferably 200:1 to 1:20.
[0042] Furthermore, the metal or metal oxide described in step (1) includes but is not limited to Bi, Bi 2 O 3 、Ge、GeO 2 、Sb、SbO 2 、Sn、SnO 2 , Al or Al 2 O 3 .
[0043] Furthermore, in step (3), the mass ratio of the carbon source material to the composite material is 1:(1-10).
[0044] Furthermore, the carbon source material in step (3) is one or more of coal tar pitch, petroleum pitch, coal-based mesophase pitch, glucose, starch, phenolic resin, chitosan, urea, sucrose, etc.
[0045] Furthermore, the equipment used for dry mixing in step (1) and step (3) is a VC mixing equipment, a V-type mixing equipment or a high-speed ball mill mixing equipment.
[0046] Furthermore, during the dry mixing in step (1) and step (3), grinding balls are added for ball milling mixing, the dry mixing time is 0.05 to 6 hours, and the ball milling speed is 50 to 2000 rpm.
[0047] Further preferably, during the dry mixing in step (1) and step (3), the grinding balls used are zirconium beads; the size of the zirconium beads is 0.1 to 5 mm.
[0048] Furthermore, the high temperature heat treatment in step (2) and step (4) is high temperature sintering.
[0049] Further preferably, during the high temperature heat treatment in step (2) and step (4), the inert atmosphere is formed by a mixed gas of one or more of nitrogen, argon and helium; the gas flow rate under the inert atmosphere is 0.2 to 5 L / min, and the ventilation time is 0.5 to 20 h.
[0050] Furthermore, the high temperature heat treatment in step (2) and step (4) is to keep the temperature at 200°C to 1000°C for 0.01h to 5h.
[0051] Further preferably, the high temperature heat treatment in step (2) and step (4) is to keep the temperature at 200°C to 400°C or 400°C to 1000°C for 0.01h to 5h.
[0052] Further preferably, the procedure for the high temperature heat treatment in step (2) and step (4) can also be: first keep the temperature at 200°C to 400°C for 0.01h to 3h, then increase the temperature to 400°C to 1000°C and keep the temperature for 0.01h to 5h, with a heating rate of 1 to 10°C / min.
[0053] Further preferably, the pressure during the high temperature heat treatment in step (2) and step (4) is (0.9 to 1.2) atmospheres, preferably normal pressure.
[0054] Furthermore, in step (2) and step (4), after the high temperature heat treatment, the excess metal, excess metal oxide or SiO2 remaining on the surface of the prepared composite material during the preparation process can be removed by pickling. 2 After pickling, rinse with water to remove residual acid on the surface of the solid product, and then dry to obtain the final product.
[0055] Furthermore, during pickling, the acid used is one or more of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, hydrofluoric acid, etc., and the concentration of the acid used can be 0.05-5 mol / L, or other common industrial pickling concentrations.
[0056] Furthermore, the pickling time is 1 to 5 hours.
[0057] Furthermore, during pickling, ultrasonic treatment is also carried out at room temperature (25±5° C.), with an ultrasonic power of 200 to 1500 W and an ultrasonic time of 1 to 10 h.
[0058] Furthermore, when washing with water, the pH value is greater than or equal to 5 and less than or equal to 8.
[0059] Furthermore, the drying is carried out using a blast drying oven, a vacuum drying oven, or a box furnace, etc., the drying temperature is 60-100° C., and the drying time is 12h-36h.
[0060] Furthermore, the present invention also provides a metal-doped modified SiO prepared by the above method. x Based on composite negative electrode material, the median particle size D 50 The size of the composite is 1 to 30 μm, and the metal elements are uniformly doped inside the silicon-based particles, while certain metal nanoclusters or particles are formed on the surface of the composite.
[0061] Further, based on a general inventive concept, the present invention also provides the metal-doped modified SiO x Application of composite negative electrode materials in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
[0062] Further, based on a general inventive concept, the present invention also provides a method for modifying SiO by using the metal doping method. x A method for preparing a lithium ion battery or a lithium ion secondary battery based on a composite negative electrode material, comprising the following steps:
[0063] a) Preparation of mixed powder: placing a certain amount of active material, binder, conductive agent and single-walled carbon nanotubes in a container to obtain mixed powder;
[0064] b) Preparation of mixed slurry: Then add solvent to the mixed powder in step a), and ultrasonically disperse it at a power of 80 to 100 W for 8 to 12 minutes, then put a polytetrafluoroethylene magnet in a container and stir it at a speed of 300 to 400 r / min for 8 to 12 hours to evenly disperse the active material, binder, conductive agent and single-walled carbon nanotubes to obtain a mixed slurry;
[0065] c) Button cell assembly: the mixed slurry in step b) is coated on a copper foil (current collector), dried at 60-80° C. for 8-12 h, and then made into a button-type electrode disc with a diameter of 12 mm; then, the prepared electrode disc is used as a working electrode, the metal lithium sheet is used as a counter electrode, and the prepared electrode disc, metal lithium sheet, diaphragm, and electrolyte are assembled into a button cell, and the battery model is a CR2032 button cell.
[0066] Specifically, the active material in step a) is the metal-doped modified SiO x Based composite negative electrode materials, or metal-doped modified SiO x / graphite composite negative electrode material, wherein metal doped modified SiO x Metal doping modified SiO in graphite / graphite composite anode materials x The mass ratio to graphite is 1:(1-10).
[0067] Specifically, in step a), the conductive agent is carbon black (Super-P) or acetylene black.
[0068] Specifically, the binder in step a) is one or more of carboxymethyl cellulose, sodium alginate, ammonium alginate, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid (PPA), lithiated polyacrylic acid (lithiated PPA), styrene-butadiene rubber and polystyrene-butadiene copolymer.
[0069] Further preferably, the binder is a mixture of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), with a mass ratio of 1:(1-2), preferably 1:1.
[0070] Specifically, the solvent is selected from one of deionized water, ethanol and NMP.
[0071] Specifically, the mass of the solvent is 1 to 3 times the mass of the mixed powder.
[0072] Specifically, in the mixed slurry obtained in step b), the weight ratio of the active material, the conductive agent, the binder, and the single-walled carbon nanotube is (80-95): (1-10): (3-10): (0.2-2).
[0073] Specifically, in step c), the diaphragm type is a polypropylene diaphragm Celgard2400, and the main component of the electrolyte used in the battery is: lithium salt (lithium hexafluorophosphate); preferably, the electrolyte is 1M LiPF added with 5% fluoroethylene carbonate FEC 6 / EC+DMC(V / V=1:1).
[0074] Specifically, in step c), the loading amount of the mixed slurry on the prepared electrode disc is 1 to 6 mg / cm 2 .
[0075] Furthermore, based on a general inventive concept, the present invention also provides a lithium ion battery or a lithium ion secondary battery prepared by the above method.
[0076] Compared with the prior art, the advantages of the present invention are:
[0077] 1. The present invention provides a metal-doped modified SiO2 which is easy to operate, has cheap raw materials and is easy to produce on a large scale. x The preparation method of the composite negative electrode material has the advantages of high commercial value and easy large-scale production.
[0078] 2. SiO prepared by the present invention x The silicon-based composite negative electrode material has obvious characteristics of metal bulk doping and surface metal cluster loading. The silicon-based particles are doped and modified by metals that can form alloys with Li. The metal clusters loaded on the particle surface can be in-situ doped into the solid electrolyte interface (SEI) during the cycle process to form an alloy with lithium ions, greatly enhancing the adsorption of lithium ions in the electrolyte and the ion transfer rate on the interface, and can also promote the interface coupling between silicon-based particles and single-walled carbon nanotubes; in addition, the metal elements doped into the silicon-based particles can effectively inhibit disproportionation and improve the conductivity of the silicon-based particles, reduce the ion diffusion energy barrier, homogenize the ion concentration field and electric field, reduce stress concentration, and effectively improve SiO x Cycling stability of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 The metal-doped modified SiO prepared in Example 1 x SEM morphology of the composite negative electrode material;
[0080] Figure 2 The metal-doped modified SiO prepared in Example 3 x SEM morphology of the composite negative electrode material;
[0081] Figure 3 The graphs are the cycle performances of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 at 1 A / g. DETAILED DESCRIPTION
[0082] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0083] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are all conventional methods; the reagents, raw materials, etc. used in the following examples, unless otherwise specified, are all conventional commercially available products and can be obtained from commercial channels.
[0084] The silicon dioxide SiO used in the following examples and comparative examples is x It is in powder form and produced by Shanghai Xiangtian Nanomaterials Co., Ltd., with the item number XT-SIO-5U. Its median particle size D50 is 5μm, and the atomic proportion of silicon is 62.5%; antimony powder (item number A572948-100g) and bismuth oxide powder (item number B105159-100g) are both purchased from Aladdin Biochemical Technology Co., Ltd.; zirconium beads (model JZ01-50) are purchased from Wuxi Jiuzhong New Materials Technology Co., Ltd., and the size of the zirconium beads is 0.1-5mm.
[0085] Example 1
[0086] Embodiment 1 provides a metal-doped modified SiO x The preparation method of the composite negative electrode material comprises the following specific steps:
[0087] 1) 10g of silicon dioxide SiO x The powder was mixed with 0.276 g of antimony powder, and 30.831 g of zirconium beads were added, and the mixture was milled in a rolling ball mill at a speed of 500 r / min for 30 min to obtain a mixture A;
[0088] 2) The mixture A in step 1) was placed in a tube furnace, the air was removed, argon was introduced, and the argon flow rate was 0.5 L / min. In the argon atmosphere, the temperature was raised to 900°C (the heating rate was 5°C / min) and sintered at normal pressure for 2 h to obtain antimony-doped SiO x Based composite negative electrode material I.
[0089] Example 2
[0090] Embodiment 2 provides a metal-doped modified SiO x The preparation method of the composite negative electrode material comprises the following specific steps:
[0091] 1) 8 g of antimony-doped SiO prepared in Example 1 x After mixing the composite negative electrode material I and 2 g of coal-based mesophase pitch (Shandong Keneng New Carbon Material Technology Co., Ltd., ash content <350 ppm, coking value ≥90%, mesophase content ≥95%), 30 g of zirconium beads were added, and the mixture was ball-milled at a speed of 500 r / min for 30 min in a rolling ball mill to obtain a mixture B;
[0092] 2) The mixture B in step 1) was placed in a tube furnace, the air was removed, argon was introduced, and the argon flow rate was 0.5 L / min. In the normal pressure argon atmosphere, the mixture was first kept at 310°C for 2 hours to soften the asphalt, and then sintered at 900°C for 2 hours to obtain antimony-doped SiO x Based composite negative electrode material II.
[0093] Example 3
[0094] Embodiment 3 provides a metal-doped modified SiO x The preparation method of the composite negative electrode material comprises the following specific steps:
[0095] 1) 10g of silicon dioxide SiO x The powder was mixed with 0.529 g of bismuth oxide powder, and 31.6 g of zirconium beads were added, and the mixture was ball-milled at a speed of 800 r / min for 10 min in a rolling ball mill to obtain a mixture C;
[0096] 2) placing the mixture C in step 1) into a tube furnace, removing air, introducing argon gas at a flow rate of 0.5 L / min, heating to 900° C. (heating rate of 5° C. / min) in an argon atmosphere at normal pressure for high temperature sintering for 2 h to obtain a composite material III;
[0097] 3) 1 g of the sintered composite material III was taken, mixed with 2.5 g of HF (mass fraction 49%) and 7.5 g of ultrapure water, and then ultrasonically treated for 4 h (ultrasound at room temperature, power of 500 W), and then centrifuged. The obtained solid was washed with ultrapure water until neutral, placed in a vacuum oven, and dried at 60 ° C for 12 h to obtain bismuth-doped SiO x Based composite negative electrode material IV.
[0098] The morphology and particle size of Examples 1 and 3 were observed using a scanning electron microscope. The SEM images obtained were as follows: Figure 1 , 2 It can be seen that the silicon oxide in the two samples still maintains a micron-scale size and a relatively rough surface. In comparison, the surface of Example 1 is smoother, while a small amount of holes appear on the surface of Example 3 due to etching.
[0099] Comparative Example 1
[0100] The original silicon dioxide SiO x The powder is directly used as negative electrode material.
[0101] Comparative Example 2
[0102] The original silicon dioxide SiO xThe powder was placed in a tube furnace, the air was removed, argon was introduced, and the argon flow rate was 0.5 L / min. The temperature was raised to 900 °C (heating rate was 5 °C / min) in an argon atmosphere at normal pressure for high temperature sintering for 2 h to obtain heat-treated disproportionated SiO x Negative electrode material V.
[0103] Comparative Example 3
[0104] Take 1g of SiO obtained after heat treatment in Comparative Example 2 x The negative electrode material V was mixed with 2.5 g HF (mass fraction 49%) and 7.5 g ultrapure water and then ultrasonically treated for 4 h (ultrasound at room temperature, power of 500 W), and then centrifuged. The obtained solid was washed with ultrapure water until neutral, placed in a vacuum oven, and dried at 60 ° C for 12 h to obtain SiO x Base negative electrode material VI.
[0105] Performance Testing
[0106] The products prepared in Examples 1-3 and Comparative Examples 1-3 were assembled into batteries and subjected to electrochemical performance tests (for the test method, refer to Wang, Haolin, et al. "What Is the Real Origin of Single-Walled Carbon Nanotubes for the Performance Enhancement of Si-Based Anodes?" Journal of the American Chemical Society 2024, 146 (25), 17041-17053). The specific method is as follows:
[0107] a) Preparation of mixed powder: The active material (the product prepared in Examples 1, 2, 3 or Comparative Examples 1, 2, 3) and the binder CMC+SBR (the mass ratio of CMC to SBR is 1:1, CMC model MAC500LC, SBR model JSR TRD104A, both purchased from Shenzhen Kejing Zhida Technology Co., Ltd.), carbon black Super-P (conductive agent, Shenzhen Kejing Zhida Technology Co., Ltd., CAS1333-86-4), and single-walled carbon nanotubes (purchased from Dongguan Kelude New Energy Technology Co., Ltd., item number MA-EN-CO-0010) are mixed in a mass ratio of 90:5:4:1 to obtain a mixed powder;
[0108] b) Preparation of mixed slurry: then add the mixed powder in step a) into a solvent (deionized water), place in a mixing container and mix evenly, the mass of the solvent is 2.5 times the mass of the mixed powder, then put a polytetrafluoroethylene magnet in the mixing container and stir at a speed of 400r / min for 10h to make the active substance, binder CMC+SBR, carbon black Super-P, and single-walled carbon nanotubes disperse evenly to obtain a mixed slurry;
[0109] c) Button cell assembly and performance testing: The mixed slurry in step b) was coated on copper foil (current collector) and dried at 80°C for 12 h to prepare a battery with a loading of 1.5 mg / cm 2 A negative electrode sheet; using a puncher or a slicer to make the prepared negative electrode sheet into a button-type electrode disc with a diameter of 12 mm;
[0110] The CR2032 button cell model was used, with a lithium metal sheet as the counter electrode, a Celgard 2400 separator, and a 1M LiPF electrolyte with 5% fluoroethylene carbonate FEC added. 6 / EC+DMC (V / V=1:1), the prepared negative electrode disc, metal lithium sheet (as counter electrode), separator and electrolyte are assembled into a button battery.
[0111] The cycle performance test was carried out under the following conditions: after activation at 0.1 A / g for 3 cycles, constant current charge and discharge cycles were carried out at a current density of 1 A / g, and the charge and discharge voltage was limited to 0.01 to 2 V.
[0112] According to the above battery assembly and testing method, the cycle performance of the negative electrode materials prepared in Examples 1 to 3 of the present invention and the negative electrode materials in Comparative Examples 1 to 3 were tested, and the performance comparison diagram was obtained as shown in FIG. Figure 3 shown.
[0113] from Figure 3 It can be seen that the antimony-doped SiO x The initial efficiency of the composite negative electrode material I is 78.8%, and the capacity retention rate after 200 cycles at 1A / g is 95.4% (1215.1 mAh / g). x The initial efficiency of the composite negative electrode material II is 84%, and the capacity retention rate after 200 cycles at 1A / g is 102.6% (1217.6 mAh / g). The bismuth-doped SiO x The first efficiency of the composite negative electrode material IV is 85.6%, and the capacity retention rate after 200 cycles at 1A / g is 96.8% (1222.3 mAh / g), while comparative examples 1-3 all show obvious performance degradation.
[0114] In summary, the metal-doped modified SiO prepared by the present invention x As the negative electrode material of lithium battery, the metal clusters loaded on the surface of the particles can be in-situ doped into the solid electrolyte interface (SEI) during the cycle, and exist in the alloy state formed with lithium ions, which greatly enhances the adsorption of lithium ions in the electrolyte and the ion transfer rate on the interface. At the same time, the metal elements doped into the silicon-based particles can effectively improve the mass transfer rate within the silicon-based particles, homogenize the ion concentration field and electric field, reduce stress concentration, and effectively improve SiO x Cycling stability of the negative electrode.
[0115] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A metal-doped modified SiO x The method for preparing a composite negative electrode material is characterized in that: The following steps are involved: 1) Dry-mixing silicon dioxide and metal or metal oxide in a certain proportion to obtain a mixture I; 2) Place the mixture I in a tube furnace, perform high temperature heat treatment under inert atmosphere and certain temperature and pressure conditions, and then cool it down naturally to room temperature to obtain metal-doped modified SiO x Based composite negative electrode materials.
2. The preparation method according to claim 1, characterized in that The molar ratio of silicon dioxide to metal or metal oxide in step 1) is 1000:1 to 1:99; the metal or metal oxide in step 1) includes but is not limited to Bi, Bi2O3, Ge, GeO2, Sb, SbO2, Sn, SnO2, Al or Al2O3.
3. The preparation method according to claim 1, characterized in that: In step 1), during the dry mixing, a carbon source material may be added; in step 1), when the carbon source material is added, the mass ratio of the carbon source material to silicon dioxide is 1:(1-10); The carbon source material in step 1) is one or more of coal tar pitch, petroleum pitch, coal-based mesophase pitch, glucose, starch, phenolic resin, chitosan, urea, and sucrose.
4. The preparation method according to claim 1, characterized in that: The high temperature heat treatment in step 2) is high temperature sintering; The high temperature heat treatment in step 2) is to keep the temperature at 200°C to 1000°C for 0.01 h to 5 h.
5. A metal-doped modified SiO x The method for preparing a composite negative electrode material is characterized in that: The following steps are involved: (1) dry-mixing silicon dioxide and metal or metal oxide in a certain proportion to obtain a mixture I; (2) placing the mixture I in a tube furnace, performing a high-temperature heat treatment under an inert atmosphere and certain temperature and pressure conditions, and then naturally cooling the mixture to room temperature to obtain a composite material; (3) dry-mixing the composite material of step (2) and the carbon source material in a certain proportion to obtain a mixture II; (4) Place the mixture II in a tube furnace and perform high temperature heat treatment under an inert atmosphere and certain temperature and pressure conditions, and then cool it naturally to room temperature to obtain metal-doped modified SiO x Based composite negative electrode materials.
6. The preparation method according to claim 5, characterized in that: In step (1), the molar ratio of silicon dioxide to metal or metal oxide is 1000:1 to 1:99; The metal or metal oxide described in step (1) includes but is not limited to Bi, Bi2O3, Ge, GeO2, Sb, SbO2, Sn, SnO2, Al or Al2O3.
7. The preparation method according to claim 5, characterized in that: In step (3), the mass ratio of the carbon source material to the composite material is 1:(1-10); The carbon source material in step (3) is one or more of coal tar pitch, petroleum pitch, coal-based mesophase pitch, glucose, starch, phenolic resin, chitosan, urea, and sucrose.
8. The preparation method according to claim 5, characterized in that: The high temperature heat treatment in step (2) and step (4) is high temperature sintering; the high temperature heat treatment in step (2) and step (4) is to keep the temperature at 200°C to 1000°C for 0.01 h to 5 h.
9. The metal-doped modified SiO prepared by the method according to any one of claims 1 to 8 x Based composite negative electrode materials.
10. The metal-doped modified SiO according to claim 9 x Application of composite negative electrode materials in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
Citation Information
Patent Citations
Negative electrode composite material with multilayer core-shell structure and preparation method and application thereof
CN110556529A
Negative electrode material containing metal-doped silicon-based composite material, preparation method and lithium battery
CN111554909A
Lithium ion battery silicon-based composite negative electrode material and preparation method thereof
CN113506861A
Simple pre-lithium metal doped silicon-oxygen-carbon negative electrode material and preparation method thereof
CN116093300A
Metal-doped silicon-oxygen-carbon material, and preparation method, application and battery thereof
CN117790801A
Cited By
Metal-doped silicon-based material and preparation method and application thereof
CN121493987A